The Relationship Of Organizational Climate And Nurse Handover To Patient Safety Incidents In Porsea General Hospital Items - Dosmaida Nababan; Tumpal Manurung; Yemima Sipahutar (International Journal of Health Engineering and Technology, 2023)
Nurses as one of the largest human resources in hospital health care institutions have an important contribution in providing nursing care. Health services can be at risk of causing patient safety incidents. This condition can be caused by the quality of the organizational climate and the ineffective implementation of handovers. The purpose of this study was to analyze the relationship between organizational climate and nurse handovers on patient safety incidents in the Porsea Hospital Inpatient Room. Analytical descriptive research design with a cross sectional approach. The sample is 45 nurses using purposive sampling. Chi Square test results obtained p-value = 0.868 There is no significant relationship between organizational climate with patient safety incidents and p-value = 0.005 There is a significant relationship between handovers and patient safety incidents. Hospitals need to pay attention to the rights of nurses, such as the issue of unequal pay and conduct ongoing evaluations of the organizational climate and the effective implementation of handovers